Dose–response association between physical activity and non-alcoholic fatty liver disease: a case–control study in a Chinese population - Li, YangFan (BMJ Open, 2019)
AIM: Physical activity plays an important role in the development of non-alcoholic fatty liver disease (NAFLD). However, the optimal intensity and dose of physical activity for the treatment of NAFLD have yet to be found. In the present study, we aimed to provide a dose–response association between physical activity and NAFLD in a Chinese population. METHODS: We recruited 543 patients with NAFLD diagnosed by abdominal ultrasonography, and 543 age-matched and sex-matched controls. The amount of physical activity, sedentary time and energy intake was collected through a structured questionnaire. Logistic regression analyses were performed to investigate the association between physical activity and NAFLD. RESULTS: After adjusting for hypertension, diabetes, body mass index, fasting blood glucose, energy intake and sedentary time, the total amount of physical activity was found to be inversely associated with NAFLD in a dose-dependent manner in men (>3180 metabolic equivalent of energy [MET]-min/week vs ≤1440 MET-min/week: OR 0.60, 95% CI 0.40 to 0.91, p for trend=0.01). In addition, both moderate-intensity and vigorous-intensity physical activity were effective in reducing the risk of NAFLD, independent of confounding variables in men (moderate-intensity physical activity: >684 MET-min/week vs none: OR 0.58, 95% CI 0.40 to 0.86, p for trend=0.01; vigorous-intensity physical activity: >960 MET-min/week vs none: OR 0.63, 95% CI 0.41 to 0.95, p for trend=0.02). CONCLUSIONS: Physical activity was inversely associated with risk of NAFLD in a dose-dependent manner in men. Vigorous-intensity and moderate-intensity physical activity were both beneficial to NAFLD, independent of sedentary time and energy intake.